RITES OF SHIFT PERFORMED BY THE MUNA ETHNIC PEOPLE IN MUNA REGENCY, SOUTHEAST PROVINCE: CONTINUITY AND CHANGE - Aso, La Aso; Kusuma, I Nyoman Weda; Ardhana, I Ketut Ardhana; Wiasti, Ni Made Wiasti (E-Journal of Cultural Studies, 2015)
Nowadays the Muna ethnic people who live in Muna Regency, Southeast Sulawesi Province can be divided into two groups; they are the Muna ethnic people who still perform the rite of shift completely, and the Muna ethnic people who perform the rite of shift partially; the letter have modified the rite of shift. The rites which are performed to show the shift in status from the time before a baby is born to the time after it is born, when someone enters childhood and adulthood, when someone is married and when someone is dead. Such rites are referred to as the rites of shift. The problems of the present study can be formulated into three; they are (1) what the rites of shift performed by the Muna ethnic group is like; (2) the factors contributing to the continuity of the rites of shift; and (3) the factors causing the change in the rites of shift performed by the Muna ethnic people to take place. This study is a qualitative study with the paradigm of cultural studies. The theory of semiotics, the theory of hegemony, and the theory of deconstruction were used in the present study. The result of the study shows that there are six forms of the rites of shift performed by the Muna ethnic people; they are the rite of what is locally referred to as kasambu (feeding or eating with the hand), the rite of what is locally referred to as kampua (the hair cutting), the rite of what is locally referred to as kangkilo (circumcision), the rite of what is locally referred to as karia (being secluded), the rite of what is locally referred to as kagaa (marriage), and the rite of what is locally referred to as mate (death). The factors contributing to the continuity of such rites are ideology and belief. And the factors causing such rites to be changed are religion, economy, education, and science and technology.
Keywords: rite of shift, Muna ethnic group, continuity, change